Use of Artificial Intelligence (AI) Technologies in Education According to Primary School Teachers: Opportunities and Challenges - Ahmet Erol; Mustafa Erol (Sakarya University Journal of Education)
Artificial intelligence (AI), which refers to technologies that mimic human cognition, affects many industries. Education is one of these sectors. Artificial intelligence affects many educational environments, from lectures to homework. In this process, both academic and ethical concerns call into question the future of artificial intelligence. These inquiries are essential as they show that the human factor will continue as an integral part of education. Because AI tools, even when best designed, can only partially replace human interaction or quality teaching. However, they can make the teacher's job easier and contribute to more effective learning. Therefore, teachers' awareness of this technology has become essential. This research aims to determine primary school teachers' opinions about using AI tools in education. The research was conducted using a case study. The participants are 16 primary school teachers determined by the criterion sampling method. Data were collected through a semi-structured interview form and analyzed with content analysis. According to the findings, teachers stated that AI tools may have advantages and disadvantages in educational environments. While teachers are concerned about the adverse effects of artificial intelligence tools on students, they also recognize their cognitive and socio-emotional contributions. Teachers also stated that artificial intelligence can make teachers' jobs easier but can only partially replace them. The results help understand primary school teachers' opinions regarding using artificial intelligence tools in the learning process.